THE PHENOMENON OF SCIENTIFIC-PEDAGOGICAL SCHOOL OF THE PROFESSORIAL INSTITUTE - Nadezda V. Karnaukh (Высшее образование в России)
The article contains the results of the author’s historicalApedagogical research aimed at forming a comprehensive vision of development of scientific-pedagogical school of Dorpat Professorial Institute. The phenomenon of scientific-pedagogical school is analyzed by the author in cultural-historical context of the 19th century as a kind of a system of prompt training of professors for Russian universities. The author presents the main features of this phenomenon. Using the method of historical simulation the author has made historical reenactment of Professorial Institute activities, which has been shown as a comprehensive pedagogical system. The article contains the characteristics of this system’s components, which conform to definition structure of “scientific-pedagogical school”: informatory, processual and evaluation-reflexive. The author marks out that the results of this model realization were followed in the work of Russian professors of a new formation: they continued the traditions of scientific-pedagogical school of Professorial Institute. It’s graduates have trained worthy students. Keeping the traditions of Russian scientificApedagogical school is one of important issues in the period of reformation of higher education in Russia.